Baselining physiological parameters in three muscles across three equine breeds. What can we learn from the horse? - Vidal Moreno de Vega, Carmen; de Meeûs d’Argenteuil, Constance; Boshuizen, Berit; De Mare, Lorie; Gansemans, Yannick; Van Nieuwerburgh, Filip; Deforce, Dieter; Goethals, Klara; De Spiegelaere, Ward; Leybaert, Luc; Verdegaal, Elisabeth-Lidwien J.M.M.; Delesalle, Cathérine (Frontiers in Physiology, 2024)
Mapping-out baseline physiological muscle parameters with their metabolic blueprint across multiple archetype equine breeds, will contribute to better understanding their functionality, even across species. Aims: (1) to map out and compare the baseline fiber type composition, fiber type and mean fiber cross-sectional area (fCSA, mfCSA) and metabolic blueprint of three muscles in 3 different breeds (2) to study possible associations between differences in histomorphological parameters and baseline metabolism. Methods: Muscle biopsies (m. pectoralis (PM), m. vastus lateralis (VL) and m. semitendinosus (ST)) were harvested of 7 untrained Friesians, 12 Standardbred and 4 Warmblood mares. Untargeted metabolomics was performed on the VL and PM of Friesian and Warmblood horses and the VL of Standardbreds using UHPLC/MS/MS and GC/MS. Breed effect on fiber type percentage and fCSA and mfCSA was tested with Kruskal-Wallis. Breeds were compared with Wilcoxon rank-sum test, with Bonferroni correction. Spearman correlation explored the association between the metabolic blueprint and morphometric parameters. Results: The ST was least and the VL most discriminative across breeds. In Standardbreds, a significantly higher proportion of type IIA fibers was represented in PM and VL. Friesians showed a significantly higher representation of type IIX fibers in the PM. No significant differences in fCSA were present across breeds. A significantly larger mfCSA was seen in the VL of Standardbreds. Lipid and nucleotide super pathways were significantly more upregulated in Friesians, with increased activity of short and medium-chain acylcarnitines together with increased abundance of long chain and polyunsaturated fatty acids. Standardbreds showed highly active xenobiotic pathways and high activity of long and very long chain acylcarnitines. Amino acid metabolism was similar across breeds, with branched and aromatic amino acid sub-pathways being highly active in Friesians. Carbohydrate, amino acid and nucleotide super pathways and carnitine metabolism showed higher activity in Warmbloods compared to Standardbreds. Conclusion:results show important metabolic differences between equine breeds for lipid, amino acid, nucleotide and carbohydrate metabolism and in that order. Mapping the metabolic profile together with morphometric parameters provides trainers, owners and researchers with crucial information to develop future studies on customized training and dietary regimens to reach full potential in optimal welfare.